PocketTouch: Through-Fabric Capacitive Touch Input - Saponas, Scott; Harrison, Chris; Benko, Hrvoje (Proceedings of ACM UIST 2011, 2011)
PocketTouch is a capacitive sensing prototype that enables eyes-free multitouch input on a handheld device without having to remove the device from the pocket of one‘s pants, shirt, bag, or purse. PocketTouch enables a rich set of ges-ture interactions, ranging from simple touch strokes to full alphanumeric text entry. Our prototype device consists of a custom multitouch capacitive sensor mounted on the back of a smartphone. Similar capabilities could be enabled on most existing capacitive touchscreens through low-level access to the capacitive sensor. We demonstrate how touch strokes can be used to initialize the device for interaction and how strokes can be processed to enable text recognition of characters written over the same physical area. We also contribute a comparative study that empirically measures how different fabrics attenuate touch inputs, providing in-sight for future investigations. Our results suggest that PocketTouch will work reliably with a wide variety of fab-rics used in today‘s garments, and is a viable input method for quick eyes-free operation of devices in pockets.